2023
DOI: 10.3390/jcm12113724
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Prehabilitation in Heart Transplant Recipients Improves Short-Term Post-Transplant Outcomes without Increasing Costs

Abstract: (1) Background and aim: This study aimed to investigate the impact of prehabilitation on the postoperative outcomes of heart transplantation and its cost-effectiveness. (2) Methods: This single-center, ambispective cohort study included forty-six candidates for elective heart transplantation from 2017 to 2021 attending a multimodal prehabilitation program consisting of supervised exercise training, physical activity promotion, nutritional optimization, and psychological support. The postoperative course was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…This review specifically addresses recent evidence related to the economics and the cost effectiveness of surgical prehabilitation. The programs reported either a reduction in healthcare related costs [10,12,14,15] or no impact on them [9 ▪ ,13,16 ▪ ,17,18 ▪▪ ], except one study, which reported no increase in costs only in a subgroup of PG [11]. However, the current studies demonstrate a heterogeneity of the programs‘ structure and of the included population, as a recent systematic review of Rombey et al also debated [6].…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…This review specifically addresses recent evidence related to the economics and the cost effectiveness of surgical prehabilitation. The programs reported either a reduction in healthcare related costs [10,12,14,15] or no impact on them [9 ▪ ,13,16 ▪ ,17,18 ▪▪ ], except one study, which reported no increase in costs only in a subgroup of PG [11]. However, the current studies demonstrate a heterogeneity of the programs‘ structure and of the included population, as a recent systematic review of Rombey et al also debated [6].…”
Section: Discussionmentioning
confidence: 51%
“…The healthcare cost reduction was mainly achieved by reducing the length of hospitalization [4,10–12,14,16 ▪ ,17]. This would also allow the hospitals to have a higher patient turnover, thus, to generate more income.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations